PENGARUH BALANCED SCORECARD, LEVERAGE, DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN (Studi Kasus pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2021-2024) - Widiatmoko, Dellen Adelya; Yuli Tri Cahyono (ITB AAS Indonesia Surakarta, 2025)
Financial performance assessment is used to measure management effectiveness in improving business performance and achieving strategic goals. Factors that affect financial performance include the balanced scorecard (BSC), leverage, and intellectual capital (IC). BSC helps overcome the limitations of financial-based measurement by offering a strategic framework that includes nonfinancial aspects and is supported by information technology. Leverage refers to the utilization of debt to increase profits, but excessive use can increase the risk of bankruptcy. Meanwhile, IC includes employee knowledge and skills that become a competitive advantage, although its measurement is still not widely standardized. The purpose of this study is to analyze the effect of balanced scorecard, leverage, and intellectual capital on financial performance. The method used in this research is quantitative method. The results of this study are Balanced Scorecard affects financial performance while, Leverage and Intellectual Capital have no effect on financial performance.